Evaluation of the potential of starter culture from Indonesian kefir grains on the characteristics of fermented milk during storage - PUTRI DIAN WULANSARI; NOVIA RAHAYU; ANDRI KUSMAYADI; RIO JATI KUSUMA (Society for Indonesian Biodiversity, 2025)
Abstract. Wulansari PD, Rahayu N, Kusmayadi A, Kusuma RJ. 2025. Evaluation of the potential of starter culture from Indonesian kefir grains on the characteristics of fermented milk during storage. Biodiversitas 26: 2368-2374. This study aims to evaluate the physicochemical quality of fermented milk produced using starter cultures derived from Indonesian kefir grains that were subcultured in goat's milk. Cow's milk was used as the raw material. The starter cultures consisted of a single strain: Lactobacillus plantarum (Orla-Jensen, 1919) Bergey et al., 1923 strains BP and DI, and Lactiplantibacillus plantarum A strain ES. Fermentation was carried out by inoculating the pasteurized milk with the cultures, followed by storage at 4°C for up to 20 days. The parameters observed during storage included pH value, total Lactic Acid Bacteria (LAB), Free Fatty Acid (FFA), acidity, and moisture content. The results showed that both the type of starter culture and the storage duration significantly affected all measured parameters. Lactobacillus plantarum strain DI produced fermented milk with the lowest pH value, and this value decreased over time. The total LAB count increased in samples inoculated with strain BP and DI but slightly decreased in strain ES during storage. FFA levels increased for all strains over time; acidity rose in samples with strains BP and DI but decreased in samples with strain ES; moisture content declined across all samples during storage. This study confirms that starter cultures derived from Indonesian kefir grains, when combined with appropriate storage conditions, significantly influence the physicochemical quality of fermented milk.